(untitled) (Scientific journal of the Fergana State University, 2024)
The article studies the issues of adequate comparability of normative indicators of motor fitness of children of primary school age with the requirements of health tests "Salomatlik". The properties of sensitive periods and the range of potential variability of structures and functions under the influence of external influences are the most significant characteristics for understanding the nature of the relationship between external influences and developing motor abilities.